2013
DOI: 10.9790/0853-0711519
|View full text |Cite
|
Sign up to set email alerts
|

Learning preferences of students studying Physiology in South India.

Abstract: Teachers of Physiology facilitate the learning of students belonging to different courses and each student has different sensory modality preferences while assimilating information. Students with a visual learning preference prefer learning with graphs and diagrams; students with an auditory preference learn by listening to information; those with a read/write preference prefer textual matter and those with a kinesthetic preference prefer to learn by physical experiences like touching and manipulating material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…[21]. Reference [22] conducted a study on physiology students in South India revealed that 55% of first year dental students preferred unimodality. This study used VARK questionnaire.…”
Section: Modality -Style/ Preference/ Strengthmentioning
confidence: 99%
“…[21]. Reference [22] conducted a study on physiology students in South India revealed that 55% of first year dental students preferred unimodality. This study used VARK questionnaire.…”
Section: Modality -Style/ Preference/ Strengthmentioning
confidence: 99%
“…One of the intrinsically complex subjects like physiology is easily understood by diverse groups of students belonging to different courses in the institutions by providing different tools of learning. [3] Considering above facts of different learning methods, therefore, the present study focuses on a holistic application in physiology by preferring different learning tools which are followed in the medical college. …”
Section: Introductionmentioning
confidence: 99%